Nutrition concepts and controversies - Sizer, Frances Sienkiewicz (Cengage, 2017)
This book explores the essentials of nutrition--including how the body breaks down and uses food, food safety, sports nutrition and special nutritional needs throughout the human life cycle--and asks you to weigh in on relevant debates, such as world hunger, chronic diseases, dietary guidelines and eating patterns. Available with the MindTap learning platform, the 15th edition also offers self-quizzing and activities to propel your learning from memorization to mastery.